First report of the leaf-mining genus Parornix Spuler from China, with descriptions of two new species (Lepidoptera, Gracillariidae, Parornichinae) - Liu, Tengteng; Wang, Encui; Jiang, Yurong; Jiang, Zhongfeng; Jiang, Bin; Teng, Kaijiang (Zootaxa, 2021)
The subfamily Parornichinae and thus the genus Parornix Spuler, 1910 are reported for the first time in China. Two new species, P. sinensis Liu, sp. n. feeding on Amygdalus davidiana and P. yuliella Liu & Teng, sp. n. on Cerasus japonica, are described herein. Both host plant species belong to Rosaceae. Adult, genitalia of both sexes, and leaf mines are described and illustrated for both species. A Maximum Likelihood tree based on DNA barcodes available for Parornix is also provided for species separation. Reference barcodes for both new species are generated.